Acute pulmonary embolism multimodality imaging prior to endovascular therapy - Sin, David; McLennan, Gordon; Rengier, Fabian; Haddadin, Ihab; Heresi, Gustavo A.; Bartholomew, John R.; Fink, Matthias A.; Thompson, Dustin; Partovi, Sasan (The international journal of cardiovascular imaging, 2021)
The manuscript discusses the application of CT pulmonary angiography, ventilation-perfusion scan, and magnetic resonance angiography to detect acute pulmonary embolism and to plan endovascular therapy. CT pulmonary angiography offers high accuracy, speed of acquisition, and widespread availability when applied to acute pulmonary embolism detection. This imaging modality also aids the planning of endovascular therapy by visualizing the number and distribution of emboli, determining ideal intra-procedural catheter position for treatment, and signs of right heart strain. Ventilation-perfusion scan and magnetic resonance angiography with and without contrast enhancement can also aid in the detection and pre-procedural planning of endovascular therapy in patients who are not candidates for CT pulmonary angiography.